We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
114
1
avatar

How do I solve this below ?? please

 

41-4[(6-2)+3(5-3)]=

 Nov 23, 2018

Best Answer 

 #1
avatar+18332 
+2

41-4[(6-2)+3(5-3)]=

41 - 4(6) + 4(2) +3(5) - 3(3) =

41 - 24 +8 +15 - 9 =    I think you can get it from here ! cheeky

 Nov 23, 2018
 #1
avatar+18332 
+2
Best Answer

41-4[(6-2)+3(5-3)]=

41 - 4(6) + 4(2) +3(5) - 3(3) =

41 - 24 +8 +15 - 9 =    I think you can get it from here ! cheeky

ElectricPavlov Nov 23, 2018

24 Online Users